2020
DOI: 10.1002/pits.22384
|View full text |Cite
|
Sign up to set email alerts
|

Perils of perfectionistic concerns among teachers

Abstract: The current study examined how teachers’ perfectionism (personal standards [PS] and concern over mistakes [COM]) relates to their achievement goals for teaching, instructional practices (creation of mastery vs. performance classroom goal structures), job satisfaction, and flow experience during teaching. The data were collected from teachers (N = 143; mean age = 43.5; 70% female; 100% European American) practicing in the Midwestern U.S. Path analyses indicated that teachers’ high personal standards predicted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In the present research study, we investigated the internal validity of the PI (Hill et al, 2004 ) in an occupation that encourages perfectionistic tendencies in own behavior or in students' behavior (Shim et al, 2020 ). Our focus on teacher perfectionism was motivated by the fact that previous studies reported that it is a powerful predictor for teacher efficiency and teacher burnout (Craioveanu, 2014 ; Ghorbanzadeh and Rezaie, 2016 ), and can have an impact on students' variables (Lozano et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present research study, we investigated the internal validity of the PI (Hill et al, 2004 ) in an occupation that encourages perfectionistic tendencies in own behavior or in students' behavior (Shim et al, 2020 ). Our focus on teacher perfectionism was motivated by the fact that previous studies reported that it is a powerful predictor for teacher efficiency and teacher burnout (Craioveanu, 2014 ; Ghorbanzadeh and Rezaie, 2016 ), and can have an impact on students' variables (Lozano et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The educational environment encourages high standards of academic achievement (Flett et al, 2009 ; Schruder et al, 2014 ), therefore it can encourage perfectionistic tendencies in students and in teachers (Gilman and Ashby, 2006 ). As part of the educational environment, teaching is a complex task that requires teachers to set achievement goals to students, and to monitor how students fulfill these goals (Shim et al, 2020 ). Despite its relevance for the outcomes of the educational environment (for a detailed discussion, see Starley, 2019 ), research on teacher perfectionism is limited (Starley, 2019 ; Shim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although students' motivation is the basic subject of research in studies in educational psychology, it is surprising that the number of studies about teacher motivation is small (Butler, 2007;Papaioannou & Christodoulidis, 2007). However, the number of studies on teachers' achievement goal orientations is increasing (George & Richardson, 2019;Li et al, 2021;S. Shim et al, 2020).…”
Section: Achievement Goalsmentioning
confidence: 99%